“We must dig our trenches, and win or die”: Voltairine de Cleyre’s Transnational Anarchism - Rita Filanti (Transatlantica)
Voltairine de Cleyre (1866-1912) was a refined poet, translator, editor, and public speaker who worked across languages to devise an American idiom for anarchist thought and action. Far from being a “foreign poison imported into the States from decadent Europe by criminal paranoiacs,” she and her comrades viewed anarchism as a direct legacy of the American literary tradition, sprouted from “native stock and soil” (Havel). In her practice as a teacher among immigrant workers in Philadelphia and Chicago, as translator from French and Yiddish, and editor of Alexander Berkman’s prison memoir, she rejected the identification of one nation with one language. Instead, her anarchism was inherently translational and her idea of nationhood multiethnic, nonpolitical, and polyglot. De Cleyre cross-fertilized anarchist ideas from overseas with the most rebellious energies of the national mind. In this way, the nation and transnationalism do not appear as alternatives, but as complementary with, and implicated in, one another. Through her writing, speaking, and practice, she enacted a transnational anarchism which was all-inclusive, non-coercive, egalitarian, and borderless, and fought for a cosmopolitan nation in which no human being and/or language would ever be foreign.